2016
DOI: 10.1007/jhep11(2016)039
|View full text |Cite
|
Sign up to set email alerts
|

Possible explanation of the electron positron anomaly at 17 MeV in 8 Be transitions through a light pseudoscalar

Abstract: Abstract:We estimate the values of Yukawa couplings of a light pseudoscalar A with a mass of about 17 MeV, which would explain the 8 Be anomaly observed in the Atomki pair spectrometer experiment. The resulting couplings of A to up and down type quarks are about 0.3 times the coupling of the standard Higgs boson. Then constraints from K and B decays require that loop contributions to flavour changing vertices cancel at least at the 10% level. Constraints from beam dump experiments require the coupling of A to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 52 publications
2
84
0
Order By: Relevance
“…For example, an important contribution to flavour-changing processes may arise from pseudoscalar-Higgs interactions or interactions between the pseudoscalar and SU (2) L gauge bosons [63]. Furthermore, in specific UV completions there may be additional non-logarithmic contributions, which become important if Λ is small, in particular if they have the opposite sign [64]. Finally, mixing between the pseudoscalar and QCD resonances may enhance the rate of rare B-meson decays for specific pseudoscalar masses.…”
Section: Model-independent Boundsmentioning
confidence: 99%
“…For example, an important contribution to flavour-changing processes may arise from pseudoscalar-Higgs interactions or interactions between the pseudoscalar and SU (2) L gauge bosons [63]. Furthermore, in specific UV completions there may be additional non-logarithmic contributions, which become important if Λ is small, in particular if they have the opposite sign [64]. Finally, mixing between the pseudoscalar and QCD resonances may enhance the rate of rare B-meson decays for specific pseudoscalar masses.…”
Section: Model-independent Boundsmentioning
confidence: 99%
“…It has been shown that in order to be compatible with existing experimental constraints, the new vector boson should be protophobic [31], i.e., the coupling to proton is highly suppressed compared with the coupling to neutron. This proposal has stimulated many related works [33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 96%
“…Also, these facilitate the simultaneous opening up of the decays χ 0 2,3 → χ 0 1 h 2 (h SM ) thus reinforcing the combined branching fractions of χ 0 2,3 to Higgs bosons over the same to Z-boson. Some specific consequences of such possibilities had been studied in the past which include rather light scalars decaying to (i) ττ and leading to soft multi-lepton final state [40], (ii) bb [41] and (iii) two photons [42,43]. For m a 1 1 GeV, even mesons can be produced out of a boosted pair of light quarks that a 1 /h 1 might decay to.…”
Section: Introductionmentioning
confidence: 99%